Traffic-related air pollution and noise and children's blood pressure: Results from the PIAMA birth cohort study. (29th August 2020) - Bilenko, Natalya; Rossem, Lenie van; Brunekreef, Bert; Beelen, Rob; Eeftens, Marloes; Hoek, Gerard; Houthuijs, Danny; de Jongste, Johan C; Kempen, Elise van; Koppelman, Gerard H; Meliefste, Kees; Oldenwening, Marieke; et al.
Abstract: Aims: Elevation of a child's blood pressure may cause possible health risks in later life. There is evidence for adverse effects of exposure to air pollution and noise on blood pressure in adults. Little is known about these associations in children. We investigated the associations of air pollution and noise exposure with blood pressure in 12-year-olds. Methods: Blood pressure was measured at age 12 years in 1432 participants of the PIAMA birth cohort study. Annual average exposure to traffic-related air pollution [NO2, mass concentrations of particulate matter with diameters of less than 2.5 µm (PM2.5 ) and less than 10 µm (PM10 ), and PM2.5 absorbance] at the participants' home and school addresses at the time of blood pressure measurements was estimated by land-use regression models. Air pollution exposure on the days preceding blood pressure measurements was estimated from routine air monitoring data. Long-term noise exposure was assessed by linking addresses to modelled equivalent road traffic noise levels. Associations of exposures with blood pressure were analysed by linear regression. Effects are presented for an interquartile range increase in exposure. Results: Long-term exposure to NO2 and PM2.5 absorbance were associated with increased diastolic blood pressure, in children who lived at the same address since birth [adjusted mean difference (95% confidence interval) [mmHg] 0.83 (0.06 to 1.61) and 0.75 (−0.08 to 1.58), respectively], but not with systolic blood pressure. We found no association of blood pressure with short-term air pollution or noise exposure. Conclusions: Long-term exposure to traffic-related air pollution may increase diastolic blood pressure in children.